Tobacco use and COVID-19 in Ghana: generating evidence to support policy and practice - Arti Singh; Divine Darlington Logo; Fiona Dobbie; Rob Ralston; Fiona Davidson; Linda Bauld; Ellis Owusu-Dabo (Journal of Global Health Reports)
# Background The COVID-19 pandemic has affected over 45 million people and caused over a million deaths globally. Tobacco use, a threat to public health worldwide, increases the risk of developing severe COVID-19 disease and death. The hand-to-mouth action, smoking-induced lung diseases, and the sharing of tobacco products such as water pipes, increase a smoker’s vulnerability to COVID-19. Implementation of tobacco control efforts in low- and middle-income countries (LMICs) including sub-Saharan Africa (SSA) is a particular challenge. The aim of this study in Ghana was to produce evidence to support governments to make informed policy decisions about tobacco control interventions in the context of COVID-19.